Properties of Nicotinamide Adenine Dinucleotide Phosphate-Dependent Formate Dehydrogenase from Clostridium thermoaceticum - Li, Lan-Fun (1966)
Li, Lan-Fun (Western Reserve University School of Medicine, Cleveland, Ohio), Lars Ljungdahl, and Harland G. Wood. Properties of nicotinamide adenine dinucleotide phosphate-dependent formate dehydrogenase from Clostridium thermoaceticum. J. Bacteriol. 92: 405–412. 1966.—A nicotinamide adenine dinucleotide phosphate (NADP)-dependent formate dehydrogenase has been isolated from C. thermoaceticum. The enzyme is very sensitive to oxygen and requires sulfhydryl compounds for activity. The apparent K(m) at 50 C and pH 7.0 for NADP is 5.9 × 10(−5)m and for formate, 2.2 × 10(−4)m. The enzyme is most active at about 60 C and at pH values between 7.0 and 9.0. The enzyme catalyzes an exchange between C(14)O(2) and formate, which requires NADP, but net synthesis of formate from CO(2) and reduced nicotinamide adenine dinucleotide phosphate could not be demonstrated. The reaction does not involve ferredoxin.